Európai Unió: alkotmányfejlődés és regionalizmus - Szilágyi, István (Tér és Társadalom, 1996)
After the ratification of the Maastrocht Treaty, the process of the European intergartion accelerated in political and legal sense. In 1995 Austria, Finland and Sweden joined the "Twelve". A further expansion of the Union and deepening the co-operation among the member states is expected. The consequences are serious organisational, political and legal-constitutional problems and conflicts and many question emerge: Will the democratic deficit of the European Union cease, can it be ceased? Will a single electoral system be created? Will the normative .... regulation of the Union come into being and what will it contain? How will the relationship between the national and supranational institutions develop? How will the principle of subsidiarity be asserted? How will the decision-making mechanism be modified? Will the fhe future single European House be organised in the form of a federation or confederation, in parliamentary or presidential system? What will the future system of regional regulation and support look like? The member states are coming to realise that the future Europe will be a Europe of the regions, and we cannot be wrong whwn forecasting the growing importance of the levels below and above the national states. This means that in the implementation and formation of the political and legal decisions fo the community integration, the "intermediate governments" of the regional and functional medium level will have a dominant role.